Implementasi Teknologi Finansial pada Layanan di Sekolah RCC Selangor, Malaysia - Asminah; Alfi Amalia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine the implementation of financial technology in services at the RCC Selangor, Malaysia. This method uses qualitative, data collection techniques are interviews, observations, and documentation. The subjects of the study were the administrators and teachers at the RCC Selangor school, Malaysia. The results of the study show that the implementation of financial technology in services at RCC Selangor school is good and has used modern technology, especially since malaysia is a developed country. RCC Selangor school implements financial technology as a service to make it easier for parents to play school fees and make it easier for teaching staff to make reports.